Within Satisfaction and Distress: Characterizing the First Cultural Transition of Young Talented Cameroonian Footballers - Boris Tachom Waffo; Denis Hauw (Current Issues in Sport Science)
Introduction Migration is at the core of today’s professional sport. In football, since 2020, the rate of migrant players has increased by 20% (Poli et al., 2024). Transnational mobility has become a highly valuable commodity making transnational football career an inescapable pathway to either professional level or world-class level. Therefore, understanding cross-borders sports mobility processes is crucial for both players and stakeholders to effectively prepare and negotiate cultural transitions. Transnational career and pathway research in sport psychology is recent, limited, and suggests that maintaining a career as a migratory athlete remains challenging (Book et al., 2021; Ryba & et al., 2016; Storm et al., 2022). By identifying challenges faced, and psychological process involved, those researches highlight at what extent culture frames athletes’ sport and non-sport life experiences. However, no studies focused on neither the first cultural transition nor African athletes. From analysis of some previous studies, it seems that the experience of the first cultural transition shapes the willingness to initiate and the experience of the following migrations (Book et al., 2021; Ryba et al., 2016). On the other hand, African countries are deeply distinct from the most other countries worldwide regarding relevant features shaping people’s life experience: social security, gross domestic product, facilities, governance, and race. Furthermore, African countries are among those displaying the highest growth of expatriate footballers (Poli et al., 2024). Additionally, most of athletic migrations from Africa correspond to forced migration (United Nations Humans Rights Council, 2022), with the difference that it is triggered by a contract. Thus, what characterize the experience of the first cultural transition of African footballers? This study aimed to explore the athletic transnational career of Cameroonian footballers to characterize their experience of the first cultural transition.